THE DEGRADATION OF MORAL VALUE ON YOUTH NARCISSISTIC TRENDS IN SOCIAL MEDIA - Ernita Dewi (Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
The development of information technology has brought about many changes in human life, especially in terms of communication. The emergence of social media that provides a lot of convenience in communicating, sharing various activities and of course being a place to share selfies, unknowingly fosters narcissism, which is no exception for teenagers. The desire to be famous, beautiful, get praise from others, seem to be natural things that must be followed. It is no doubt that this narcissistic can have negative impacts on a person's behavior and morals. Taking photos in inappropriate clothes, or speaking in inappropriate language, seems to be justified on social media. Not to mention that the narcissistic photo implies a person's arrogance, because it is presented as perfectly as possible so that other people are interested and become viral, regardless of its consequences for moral values.